Orobanche purpurea on its newly discovered site near Zatoń Dolna (NW Poland): the problem of protection of a threatened parasitic plant species - Prajs, Bożena (Biodiversity: Research and Conservation, 2011)
A newly discovered local population of Orobanche purpurea in NW Poland is described. It was composed of 141 specimens when first found in 2007 on fallow land near the village of Zatoń Dolna. However, the size and distribution of this population changed considerably during the last three growing seasons. The remarkable decline in population size is probably due to competition of other species with the host plant, Achillea millefolium, and the effect of the parasite itself, which weakens its host.